2022
DOI: 10.3389/fmicb.2022.993214
|View full text |Cite
|
Sign up to set email alerts
|

Leguminous cover crops and soya increased soil fungal diversity and suppressed pathotrophs caused by continuous cereal cropping

Abstract: The enrichment of soil-borne fungal pathogens and a high input of mineral fertilizer in the continuous cropping of cereal crops have raised a concern about soil health deterioration. Conversion of continuous cereal cropping to a legume-involved system alters the soil fungal community. However, when a leguminous cover crop is grown with a succeeding legume grain crop such as soya (Glycine max L. Merril), the effects on the soil fungal community when two legumes are involved in the crop system remain unclear. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…10. 3389/fmicb.2024.1405842 Frontiers in Microbiology 10 frontiersin.org beneficial alterations to the soil habitat due to the presence of cover crop to host more diverse fungal taxa, supporting the notion that cover crop can enrich soil biodiversity and function (Jousset et al, 2017;Yu et al, 2022). The positive correlation between enhanced fungal richness and critical sunflower growth metrics highlights the potential benefits of a diverse fungal community for plant productivity, a finding that echoes the work of Zhang et al (2022) on the role of fungal diversity in plant growth.…”
Section: Discussionmentioning
confidence: 78%
“…10. 3389/fmicb.2024.1405842 Frontiers in Microbiology 10 frontiersin.org beneficial alterations to the soil habitat due to the presence of cover crop to host more diverse fungal taxa, supporting the notion that cover crop can enrich soil biodiversity and function (Jousset et al, 2017;Yu et al, 2022). The positive correlation between enhanced fungal richness and critical sunflower growth metrics highlights the potential benefits of a diverse fungal community for plant productivity, a finding that echoes the work of Zhang et al (2022) on the role of fungal diversity in plant growth.…”
Section: Discussionmentioning
confidence: 78%
“…In terms of fungal function prediction, straw application increased symbiotroph and pathotroph relative abundance; however, increased pathotroph abundance is negative for soil health, which may be related to the texture of saline soils. Yu et al 2022 suggested that legume cover crops can suppress pathotrophic fungal microorganisms [ 2 , 64 ], which could inform further saline improvement trials later. We concluded that the implementation of straw returning resulted in a notable enhancement in the abundance and diversity of soil fungus, as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Curvularia is the main pathotroph in tobacco leaves and is detrimental to crop quality ( Fajola, 1979 ). Saprotrophs have antagonistic effects with pathotrophs ( Yu et al, 2022 ), which may be the reason why the main pathotrophs in tobacco leaves, Curvularia , increased with a decrease in saprotrophs, Filobasidium , in the early stage of the AC process. Curvularia reached its maximum in the yellowing stage, which is also the stage of massive water loss in tobacco leaves.…”
Section: Discussionmentioning
confidence: 99%